Kajian Struktur Visual Pada Pasca Produksi Film Eksperimental “Sweet Rahwana” - Sasongko, Hery (Fakultas Film dan Televisi - Institut Kesenian Jakarta, 2023)
Experimental Film “Sweet Ravana” is a film artwork that raises about human nature that is translated through puppet approach. To realize the character in accordance with one of the human traits that exist in the puppet characters namely Ravana. Where Ravana is a figure of evil and always thirsty for power. In a movie there are some messages to be conveyed by the author. The message to be conveyed apart from the narrative aspect also through the cinematic aspect. In the experimental film